2021
DOI: 10.1021/acs.jpcc.1c06869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diffusion on Photo-Induced Excited-State Energy Transfer between Fluorescent Semiconducting Molecules: Tris-(8-hydroxyquinoline) Aluminum and 6,13-Bis (Triisopropylsilylethynyl) Pentacene

Abstract: In the present work, the effect of diffusion on photo-induced excitation energy transfer between fluorescent organic semiconducting molecules tris-(8hydroxyquinoline) aluminum (AlQ 3 , n-type donor) and 6,13-bis (triisopropylsilylethynyl) pentacene (TIPS-P, p-type acceptor) at a concentration range of 10 −4 to 10 −6 M in chloroform solution was studied by steady-state and time-domain fluorescence measurements. The donor−donor interaction strength is significantly weaker than the donor−acceptor strength (the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…In our previous study, we observed a long decay time in the case of acceptor decay dynamics, which is not observed in the present case. The acceptor for that case was the same as in the present case (TIPS-P).…”
Section: Resultscontrasting
confidence: 73%
See 4 more Smart Citations
“…In our previous study, we observed a long decay time in the case of acceptor decay dynamics, which is not observed in the present case. The acceptor for that case was the same as in the present case (TIPS-P).…”
Section: Resultscontrasting
confidence: 73%
“…Finally, based on the above experimental analysis, a schematic mechanism for excitation energy transfer between the excited state of F8BT and the ground state of TIPS-P in chloroform solution is shown in Scheme through the energy-level diagram. Unlike AlQ3/TIPS-P, EET took place in the present system via both the FRET and RET mechanisms. Briefly, the mechanistic aspect of EET revealed in the present study would be important in designing efficient photovoltaic systems. …”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations